Additions to the Colombian Anacroneuria fauna (Plecoptera: Perlidae) with descriptions of seven new species - Zúniga, Maria del Carmen (Illiesia, 2007)
Seven new species are described from Colombia: Anacroneuria citara, A. otun, A. pastora, A. quimbaya, A. tatama, A. tayrona and A. tunasi. The first Colombian records are given for A. bari Stark, A. curiosa Stark and A. harperiStark; the latter two species were previously known from Mesoamerica and this is their first report from South America. New records, mainly in the Andinum natural region, are presented for 20 previously reported Colombian species. In addition, the unknown females of A. calima Baena & Rojas, A. martaZúniga & Stark and A. yameo Stark & Sivec are described, and three unassociated females are described under informal designation.
Keywords: insekti; Plecoptera; vrbnice